Is Physical Activity a Risk or Protective Factor for Subsequent Dietary Lapses among Behavioral Weight Loss Participants? - Crochiere, Rebecca J. (Health Psychol, 2020)
OBJECTIVE: Dietary lapses drive weight loss failure, and specific factors influence risk of lapse. Physical activity (PA) may be one such risk factor, though whether PA increases or decreases appetite, and thus risk of lapse, is unclear. In fact, most studies examining the relation between PA and energy intake are limited by use of laboratory-based settings, intensive PA manipulations, and healthy-weight samples. This study aimed to maximize ecological validity by examining the extent to which free-living PA of various intensities prospectively predicts same-day dietary lapses among individuals enrolled in a weight loss program. METHODS: Participants were 130 adults with overweight/obesity in a behavioral weight loss treatment instructed to follow a PA and dietary prescription. At mid-treatment, moderate-to-vigorous PA (MVPA) and light PA were measured using hip-worn Actigraph GT3X+ accelerometers. Lapses were assessed using ecological momentary assessment. RESULTS: Within-subject total PA (b = −0.012, SE = 0.005, p =.01) and light PA (b = −0.014, SE = 0.006, p =.01) negatively predicted lapse. MVPA followed the same pattern, but the effect was not statistically significant (b = −0.013, SE = 0.009, p =.12). CONCLUSIONS: This study was the first to investigate if objectively measured PA prospectively predicts lapse from a weight loss program. Results suggested that for every additional 10 minutes of total PA one engaged in, the risk of lapse decreased by 1%.